DRIED OUTDOOR THROUGH PILED IN EASEL AND HORIZONTAL FERNANSANCHEZ SQUARE (Triplaris cumingiana Fish. Mey.) And laurel (Cordia alliodora Ruiz y Pav.) IN QUEVEDO CITY, ECUADOR - Troya Mera, Fidel Antonio (2009)
During five months wood drying defects were evaluated: curled up, warped, twist, cracks, superficial fissures; as well as the moisture content balance in the fernansánchez (T. cumingiana) and laurel (C. alliodora) woods. Two piling up methods were compared: easels and horizontal squares, in the drying of boards of three sections of the tree (basal, middle and terminal). There were not significant differences between the piling up methods neither among the sections of the tree. It was determined that it is enough with 90 days of outdoors drying for the wood of both species to reach the moisture content balance of the area where the investigation was carried out.